Konsep Sistem Customer Relationship Management Pada Toko Penjualan Produk - Antika, Siska; Hambali, Hambali; Akmal, Akmal (Building of Informatics, Technology and Science (BITS), 2022)
The product sales system in the store still uses a manual system in marketing its products, so only certain people know about the product. Stores cannot know their customers and who are the best customers, nor can they know when and how customers buy. In this case the author uses the method of Customer Relationship Management (CRM) which allows the correct and effective information culture and relationship technology. With the construction of this system, it is hoped that later they will be able to find out who the best and profitable customers are, be able to predict what customers can get or which products they will buy in the future and can interact in real time by integrating web technology developments in improving the quality of product sales. at the gift shop of the range. Customer Relationship Management (CRM) is a company strategy used to please customers or customers so they don't turn to competitors. The product sales system at Anugrah Kisaran Store is built using the PHP and MySQL programming languages ​​as its database, as well as tools used to describe the system model. is the Unified Modeling Language (UML). This system will only be intended for Anugrah Kisaran Stores. Customer Relationship Management (CRM) will provide the best services to customers such as product information, payments will be easier and faster to access